Iguanaz Productions Sdn. Bhd. / Puteri Yasrina Mohd Yusoff ... [et al.] - Mohd Yusoff, Puteri Yasrina; Misran, Noor Aida; Ismail, Siti Nur Arnee; Ishak, Nor Suriani; Musa, Nur Risyah (Faculty of Communication and Media Studies, 2002)
Iguanaz Productions Sdn. Bhd. is a private limited company. It will be incorporated by June 30th, 2005. This company has five colleagues and each person has their own experiences in handling the production equipments and the process of productions. With some knowledge on the basic of marketing and business, it will much easier for us to manage our company.